APLIKASI PENERIMAAN BUKU TAMU BERBASIS WEB PADA KANTOR KECAMATAN GUMELAR - NOVITA SETIANTI; Wika Purbasari; Sunaryono Sunaryono; Melia Kurniasih (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2023)
Abstract – Gumelar sub-district still uses manual processes and is not computerized. Therefore we need a computerized application program. This study uses the RAD (Rapid Application Development) method. The results of the reliability test show that the Cronbach Alpha value is 0.801 in the product test variable and 0.862 in the benefit test variable, which means 0.7. This means that the product test and benefit test systems are reliable. The results of product testing with the Dimension.Quality for Goods attribute get a percentage of 95.6 %, which is more than 75%, so it can be concluded that the product testing has been successful. The results of the benefit test with the ULEA attribute get a value of 95%, which is more than 75%, so it can be concluded that the benefit test has been successful. Based on product testing and benefits, it can be concluded that in Gumelar District, a web-based guest reception application can be applied.